2021
DOI: 10.3390/tropicalmed6020071
|View full text |Cite
|
Sign up to set email alerts
|

Blood Culture Testing Outcomes among Non-Malarial Febrile Children at Antimicrobial Resistance Surveillance Sites in Uganda, 2017–2018

Abstract: Blood culture (BC) processes are critical to the utility of diagnostic testing, bloodstream infection (BSI) management, and antimicrobial resistance (AMR) surveillance. While Uganda has established BC guidelines, often laboratory practice does not meet the desired standards. This compromises pathogen recovery, reliability of antimicrobial susceptibility testing, and diagnostic test utility. This study assessed laboratory BC process outcomes among non-malarial febrile children below five years of age at five AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 28 publications
6
3
0
Order By: Relevance
“…This study found a high prevalence of E. coli, P. aeruginosa , and S. aureus . These findings are similar to those of many short-term researcher-driven studies earlier done at MH, which stated a high prevalence of the same species [ 9 15 ]. These species continue to cause the commonest community- and hospital-acquired bacterial infections [ 9 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This study found a high prevalence of E. coli, P. aeruginosa , and S. aureus . These findings are similar to those of many short-term researcher-driven studies earlier done at MH, which stated a high prevalence of the same species [ 9 15 ]. These species continue to cause the commonest community- and hospital-acquired bacterial infections [ 9 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar to those of many short-term researcher-driven studies earlier done at MH, which stated a high prevalence of the same species [ 9 15 ]. These species continue to cause the commonest community- and hospital-acquired bacterial infections [ 9 15 ]. But, these species could be used as surveillance markers for AMR in this setting as has been shown [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations